Can antioxidant's reactive oxygen species (ROS) scavenging capacity contribute to aged seed recovery? Contrasting effect of melatonin, ascorbate and glutathione on germination ability of aged maize seeds. (3rd October 2017) - Deng, Benliang; Yang, Kejun; Zhang, Yifei; Li, Zuotong
Abstract: It is well known that antioxidants such as AA (reduced ascorbate), glutathione (GSH) (reduced glutathione) and melatonin can delay seed ageing. Can they recover aged seed? Artificial aged maize seeds were obtained and their reduced germination rate (GR) and high lipid peroxidation were recorded. Exogenous melatonin was applied on these aged seeds and enhanced GR was observed. However, treatment with other antioxidants such as AA, GSH or DMTU (dimethyl thiourea) did not significantly improve or even reduce the GR of aged seeds. In addition, melatonin improved germination ability of theses aged seeds can be significantly impaired by DDC (diethyldithiocarbamic acid, a specific inhibitor of superoxide dismutase or superoxide dismutase (SOD)) and ATZ (aminotriazol, a specific inhibitor of catalase or CAT). In a further study, we found that melatonin but not other antioxidants (AA, GSH and DMTU) significantly induced CAT and SOD activities of aged seeds after imbibition. Accordingly, melatonin significantly reduced lipid peroxidation in aged seeds than that of other antioxidants. Taken together, these data suggest that melatonin induced antioxidant enzyme but not its direct reactive oxygen species (ROS) scavenging capacity contributing to recovery of aged maize seeds.